2020
DOI: 10.3390/info11010038
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Feature Aggregation and Combination for Two-Dimensional Ensemble Feature Selection

Abstract: Feature selection is a way of reducing the features of data such that, when the classification algorithm runs, it produces better accuracy. In general, conventional feature selection is quite unstable when faced with changing data characteristics. It would be inefficient to implement individual feature selection in some cases. Ensemble feature selection exists to overcome this problem. However, with the advantages of ensemble feature selection, some issues like stability, threshold, and feature aggregation sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, as mentioned previously, to the best of our knowledge, stability of FS has not been considered in the field of PdM, including the various industrial processes, components, and monitoring tasks existing in this field. A recent topic that has been studied in conjunction with the stability of FS is the homogeneous ensemble of FS [14], [23], [40]- [42]. It has been studied in many domain areas, mainly with the aim of improving the FS stability.…”
Section: Related Workmentioning
confidence: 99%
“…However, as mentioned previously, to the best of our knowledge, stability of FS has not been considered in the field of PdM, including the various industrial processes, components, and monitoring tasks existing in this field. A recent topic that has been studied in conjunction with the stability of FS is the homogeneous ensemble of FS [14], [23], [40]- [42]. It has been studied in many domain areas, mainly with the aim of improving the FS stability.…”
Section: Related Workmentioning
confidence: 99%
“…Several research contributions have been done to improve the ensemble methods which currently remain a major challenger of deep learning which is most used [21]. Recently, many studies [40][41][42][43] have shown that the combination of ensemble models with preprocessing techniques improves performance in modeling of the unbalanced classification problem. For a CRM dataset such as bank churn data having heterogeneous features and imbalance classes, appropriate data preprocessing is necessary to have the best model performance.…”
Section: The Proposed Approachmentioning
confidence: 99%
“…The idea behind this is that, by flipping the bits, there is a possibility of de-selecting an irrelevant or redundant feature as well as a possibility of selecting a highly relevant feature. The presence of these irrelevant or redundant features causes a degradation in the classification performance (Alhamidi, 2020;Mafarja, 2019). Therefore, performing this perturbance provides room for possible improvement.…”
Section: One-way Local Search (Exploitation Only)mentioning
confidence: 99%